Technical actions of English academy football players within variety of small-sided games - Conway, K.; Smith, S (Scientific Journal of Sport and Performance, 2025)
In English professional football academies, each club assigns a specific game format to each age group`s fixtures. However, there is uncertainty about how these formats impact technical actions and skill development in youth academies. This study aimed to examine the frequency of technical actions in an elite football academy across two common game formats used in the Foundation Phase age-groups (Under-9 to Under-11). The research focused on both small-sided games (SSGs) and regular-sided games (RSGs) within a Category One Football Academy. Participants were video recorded playing forty minutes each in their designated SSG and RSG formats, with nineteen technical actions observed and analysed. The results showed a statistically significant difference in fifteen technical actions between the two formats, with an increase in all these actions during SSGs. Notable technical actions such as one-touch shots, receiving a pass under pressure, and players beaten through a dribble significantly increased in SSGs. Another action, players beaten through a forward pass (packing score), saw a rise in RSGs, though this was not statistically significant. These findings suggest SSGs are beneficial for enhancing technical skills such as shooting, receiving under pressure, and dribbling, while RSGs may better develop forward passing abilities.